Scientific Objectivity and Its Contexts - Agazzi, Evandro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The first part of this book is of an epistemological nature and develops an original theory of scientific objectivity, understood in a weak sense (as intersubjective agreement among the specialists) and a strong sense (as having precise concrete referents). In both cases it relies upon the adoption of operational criteria designed within the particular perspective under which any single science considers reality. The (3z(Bobject(3y (Bso attained has a proper ontological status, dependent on the specific character of the criteria of reference (regional ontologies). This justifies a form of scientific realism. Such perspectives are also the result of a complex cultural-historical situation. The awareness of such a (3z(Bhistorical determinacy(3y (Bof science justifies including in the philosophy of science the problems of ethics of science, relations of science with metaphysics, and social dimensions of science that overstep the traditional restriction of the philosophy of science to an epistemology of science. It is to this (3z(Bcontext(3y (Bthat the second part of the book is devoted.s
Historical and Philosophical Background -- The Characterisation of Objectivity -- First Corollaries in the Philosophy of Science -- The Ontological Commitment of Science -- Scientific Realism -- The Contexts of Objectivity -- Corollaries in the Philosophy of Science -- Scientific Truth Revisited -- The Context of Making Science -- Science and Metaphysics -- Appendix -- References -- Indexes.
Keywords: Philosophy; Ethics; Philosophy and science; Philosophy of nature; Mathematical logic; Physics; Philosophy; Philosophy of Science; History and Philosophical Foundations of Physics; Mathematical Logic and Foundations; Ethics; Philosophy of Nature; Electronic books